Pengembangan E-LKPD Berbasis Live Worksheets pada Pembelajaran Tematik Terpadu Kelas V Sekolah Dasar - Apfani, Sry; Anggraini, Dwi (LP2M Universitas Adzkia, 2023)
This research is motivated by the lack of motivation of students and to increase the effectiveness of students in doing the tasks that exist in the LKPD given by the educator. So that students are less active in the learning process. Along with the development of the era of technology in the field of information and communication and supported by the advancement of the internet, this also has an impact on the development of types of learning resources. The purpose of this research is to see the development of E-LKPD based on live worksheets in integrated thematic learning for fifth grade elementary school. This type of research is development research (R&D) using a 4D model (Define, Design, Development, Dissemination). Based on the results of the validation in terms of the material obtained a value of 84.3% (valid), in the language aspect it obtained a value of 82.1% (valid), and in the display aspect with an average value of 95% (very valid). The practicality level of E-LKPD from educators with an average value of 89.3% (very practical), and the practicality level of E-LKPD by students reaching an average value of 87.2% (very practical). The value of the effectiveness of the E-LKPD with an average of 88 obtained from the E-LKPD filling test by students Thus, it can be concluded that the E-LKPD based on live worksheets in Integrated Thematic Learning for Grade V Elementary School is valid, practical, and effective.